Cloud Computing and Hyperscale Data Centers: A Comparative Study of Usage Patterns - Ma, Yu; Shen, Zhixuan; Shen, Jinnian (Journal of Theory and Practice of Engineering Science, 2024)
The rapid growth of cloud computing and hyperscale data centers has transformed the way we store, process, and manage data. Understanding usage patterns is crucial for optimizing resource allocation, performance, security, and costs in these environments. This paper explores the similarities and differences between cloud computing and hyperscale data centers, highlighting their implications for users and providers. We discuss the importance of understanding.